AGAMA, MEDIA, DAN MASYARAKAT DI ERA DIGITAL - Andriyana, Putri; Adrian, Bob (Borneo : Journal of Islamic Studies, 2024)
In the digital age, digital media, particularly the internet and social media, have significantly changed the landscape of communication and social interaction. The ease of access to information, the ability to participate in discussions, and the formation of virtual communities are some of the positive impacts of this technological development. In addition, digital technology shapes worship practices and enhances communication and connectivity among individuals. The role of digital technology brings a variety of benefits in terms of access to information and social interaction. It is important to continue to pay attention to and ensure that the use of digital technology is responsible and provides benefits to society as a whole. This research examines the correlation between religion, mass media, and society. The research results showed that the correlation between technological progress, especially mass media, and human life has both good and bad sides. Mass media plays an important role in spreading religious messages and increasing public understanding, but it can also have negative impacts, such as the spread of false information. It is important to use mass media wisely and monitor them to minimize their negative impacts.